Linking transformational leadership to firm innovativeness - Poespowidjojo, Donny Abdul Latief; Ramli, Azahari; Kamaruddeen, Ahmed Mohammed; Bakar, Muhammad Shukri; Shakir, Khairunnisah Ahmad (DIVA ENTERPRISES PVT. LTD.., 2018)
The leadership style of the top management can have a significant effect on the innovativeness of the firm. The purpose of this study is to examine the impact of a particular leadership style, transformational leadership, on innovations among logistics companies. Drawing on a sample of 500 logistics companies were randomly selected and given the questionnaire to complete. A total of 86 questionnaires were returned and 84 questionnaires were useable for analysis. Findings revealed transformational leadership has a significant relationship and positive impact on innovativeness of logistics companies. The implication of the study brings new evidence to bear on the notion about the innovativeness in the logistics industry in Malaysia.